IMPLEMENTASI MODEL PEMBELAJARAN TEMATIK BERBASIS COOPERATIVE LEARNING KELAS II DI MI NU KESESI - Akmal, Alfina Amaliyatul; Rohmaniyah, Zulfatur; Ristiyanti, Lina (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Thematic learning is a learning activity that integrates material from several subjects in one theme/topic of discussion. Thematic learning will provide integrated learning opportunities that place more emphasis on student participation/involvement. A teacher who wants the teaching and learning process to be successful must be able to choose and determine the thematic learning model that will be used in the teaching and learning process, so that it can stimulate the enthusiasm of each student to be actively involved in their learning experience. This research aims to describe how the class II thematic learning model is implemented at MI NU Kesesi. This research method uses a descriptive qualitative approach with a field research type where data collection techniques use observation, interviews and documentation. The collected data was analyzed through 3 stages, namely data reduction, display and data verification. The results of this research show that the implementation of thematic learning carried out at MI NU Kesesi using the cooperative learning model is considered to be very appropriate to the conditions of the students and the students' abilities, which can be seen from the great enthusiasm of the students in participating in learning when using the cooperative learning model. . And the teacher attracts students' activity by asking questions about the material and relating it to everyday life.